The Timeless Cork Design in Portugal: on the Cutting Edge of Sustainability - Duarte de Almeida, I.; M.J. Delgado; Gianni Montagna; Luís Ramos (Congress PHI 2022 FA - Time and Space, 2022)
Cork is a natural, recyclable, non-toxic and renewable resource obtained from the bark of the cork oak (Quercus suber L.). Its unique properties make cork one of the most versatile and mind-blowing materials and an excellent choice for designing sustainable products and creating new spaces. This paper looks at the efforts of the Portuguese cork Industry (PCI) to change the paradigm of cork use. From the traditional and ancient use of cork to an era where sustainability is the future, sustainable cork products are now emerging with brand-new designs following a circular economy model (CE). Interviews with CEOs, designers, architects and academic experts from the PCI mainframe provided a fruitful discussion on the benefits of using cork products for a sustainable future. Despite being considered a 'green' sector, the results showed that PCI does not fully utilize the CE model. Furthermore, the results identify CE drivers and barriers to rethinking eco-design in the PCI and show that the PCI sector benefits from a CE paradigm because the cork industry is sustainable and can innovate and develop new products. However, implementing CE is difficult as most companies focus on cork stoppers and lack the financial resources to acquire new Industry 4.0 (I4.0) facilitating technologies for a productive and creative paradigm shift.